Disagreements. Semantics, Pragmatics and Existence - Losada, Alfonso (2015)
In this article, we defend the existence of disagreements in areas of discourse that involve anagent’s perspective, as the semantic theory known as “Radical Relativism” putsit. In the face of the idea that such disagreements exist and can only be explainedby a radical relativist semantics, contextualist theorists have offered arguments to deny their existence or to provide an explanation of them which does not imply departing from the standard semantic theory. These arguments will be our targetof criticism. We raise the debate in terms of the distinction between semantic andpragmatic aspects of disagreement, and we defend a simple vision of disagreement, which we believe the relativist must have in mind if he wants to argue that disagreements belonging to areas that involve an agent’s perspective can count as evidence in his favor.